COPING STRATEGY IN TRANSPORTATION BUSINESS: CASE STUDY ON PUBLIC TRANSPORTATION IN BEKASI REGENCY - Christien Simorangkir; Maria Agape Widya Prasetya; Nirvara Dinta Pirenaningtyas; Ignatya Larasati; Dhian Adhitya (Riset Ekonomi Pembangunan, 2021)
Corona Virus Disease 2019 (COVID-19) which originated from Wuhan, China has been addressed by the World Health Organization (WHO) as a global pandemic. The emergence of COVID-19 gives impact to the health of all people and the Indonesian economy. One of the economic sectors affected is the public transportation business. This study aims to explore the impact and how to survive in the public transportation sector amid COVID-19 pandemic. This study used a qualitative descriptive analysis with a case study method in Bekasi Regency, with data collection techniques of online and direct interviews. Based on the results of this study, it can be concluded that the impact of COVID-19 on public transportation businesses is a decrease in the amount of income and a decrease in the frequency of passengers. Every business actor has a different strategy for survival.